An investigation of frequency scanning interferometry for the alignment of the ATLAS semiconductor tracker - Coe, PA (2001)
The relative alignment of the silicon detector modules of the ATLAS semiconductor tracker will need remote monitoring during operation, within a high radiation environment. A geodetic grid of distance measurement fibre-coupled interferometers will monitor changes in the shape of the support structure. Eight hundred fibre-coupled grid line interferometers (GLIs) will be compared simultaneously to a stable, evacuated reference interferometer using Frequency Scanning Interferometry (FSI). The GLIs, (from 70 mm to 1400 mm long, with pW level return signals) must be measured to a precision of 1 micron, to reconstruct the grid shape, in three dimensions, to a precision of 10 microns.